VARIATIONAL METOD APPLIED IN CALCULATION OF KEY JOINT’S STRENGTH IN THE CURRENT CONSTRUCTION SYSTEMS - Dovzhenko, О.; Pogribnyi, V.; Chursa, Yu. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article deals with construction precast and precast with cast-in-place framebuildings, which elements’ combined action is provided by key joints, are widely used.The paper is devoted to the key joints, taking up considerable transverse forces. Standardmethods of their calculation are imperfect, they do not take into account all factors of influenceand cause significant underestimation of the joint’s strength. At Poltava National TechnicalYuri Kondratyuk University a calculation methodology has been developed, which, beinggeneric enough, takes into account the destruction’s character and a set of influence factors.Three- and five-key joints of multi-storey building’s reinforced concrete frame’s elements havebeen considered. An example is given of determining the strength of the capillary’s joint withthe column of the precast flat slab floor by means of the variational method in the concreteplasticity theory. The obtained results are compared to the standard calculations.Keywords: joint, key, strength, plasticity, shear, concrete.